Rooting knowledge for feeding the planet - Petruzzella D.; Sancassiani S.; Concia F.; Giannelli M. (Feeding knowledge, 2017)
The Programme, which contributed to building up Expo Milano legacy, dealt with the importance of cooperation on research and innovation for food security in the Mediterranean. “Feeding Knowledge” constitutes an interesting model for testing innovative knowledge sharing and co-creation methods through the involvement of all the stakeholders of the food security “innovation chain”, from farmers to extension services, to academia and decision makers. Thanks to the support of the on-line ecosystem www.feedingknowledge.net, the Programme has developed a mechanism for sharing needs, problems, knowledge and best practices aimed at enabling research to provide concrete solutions to local problems. This paper presents “Feeding Knowledge” concept, philosophy and main results, which largely contributed to the creation of an effective knowledge system in the Mediterranean.
Expo Milano 2015